Regional earth science information in local water management : earth science information needs in local government water control master planning : a study of ASCE Urban Water, Resources Research Council - McPherson, M. B. (Murray Burns); American Society of Civil Engineers (New York : American Society of Civil Engineers, 1975)
Includes bibliographical references.